(untitled) (International Journal of Environmental Sciences, 2025)
This study examines how the introduction of financial technology, or fintech, affects the financial behavior of Gen Z and Millennials in India, two of the most tech-savvy and connected generations. Through investment apps, digital wallets, mobile banking, and the Unified Payments Interface (UPI), fintech has completely changed how people can access financial services. Using the Technology Acceptance Model (TAM) as a theoretical framework, the study examines how perceived utility and usability affect the uptake of fintech products (Davis, 1989). To find trends in digital financial behavior, financial inclusion, social media influence, and financial literacy, a primary survey with 200 respondents was carried out. The analysis, supported by graphical presentations and percentage-based insights, reveals that FinTech tools significantly enhance financial inclusion and promote effective money management among Indian youth (RBI, 2022; Bansal & Kumari, 2020). Visual data indicate that over 75% of respondents rely on digital payment and investment platforms for routine transactions, demonstrating high adoption rates. However, challenges such as limited financial literacy and increasing dependence on digital applications persist. A notable finding from the percentage distribution is the growing influence of social media on financial choices—often blurring the line between informed decision-making and peer-driven behavior (Mehta & Sharma, 2021). Importantly, the study also introduces the emerging role of sustainability-focused fintech innovations, particularly through the concept of a green wallet. This digital solution encourages environmentally responsible spending and investing by tracking carbon footprints, promoting paperless transactions, and offering incentives for eco-friendly purchases. Such innovations align youth financial behavior with climate-conscious values. The findings have critical implications for fintech developers, financial educators, and policymakers in creating secure, inclusive, and sustainable digital finance ecosystems. This research contributes to the evolving discourse on digital finance by illuminating both the behavioral trends and the sustainability potential within India’s digitally empowered youth population.